The lightning thief - Riordan, Rick. (New York : Disney/Hyperion Books, 2010)
After learning that he is the son of a mortal woman and Poseidon, god of the sea, twelve-year-old Percy is sent to a summer camp for demigods like himself, and joins his new friends on a quest to prevent a war between the gods.
4.9
5-8
Keywords: Camps -- Juvenile fiction; Gods -- Juvenile fiction; Jackson, Percy (Fictitious character) -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Camps -- Fiction; Gods -- Fiction; Jackson, Percy (Fictitious character) -- Fiction; Voyages and travels -- Fiction; Camps -- Fiction; Gods and goddesses -- Fiction; Jackson, Percy (Fictional character) -- Fiction; Voyages and travels -- Fiction